Forming a Cultured Generation: Training in Language Politeness and Literary Appreciation at SMA Negeri 3 Gowa: Membentuk Generasi Berbudaya: Pelatihan Kesantunan Berbahasa dan Apresiasi Sastra di SMA Negeri 3 Gowa - Munirah Hasjim; Nurhayati Nurhayati; Inriati Lewa; Takko Bandung; St. Nursa’adah; Faisal Oddang; Indarwati Indarwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Politeness in language and appreciation of literature are important aspects in the formation of the character of the younger generation, especially in the era of globalization that is vulnerable to the degradation of cultural values. This community service aims to increase the awareness of students of SMA Negeri 3 Gowa Regency of the importance of polite speech and understanding of cultural values ​​through literary works. The methods used include interactive training, group discussions, and analysis of literary texts based on local wisdom. The results show a significant increase in students' ability to appreciate literature and the application of politeness in language in everyday interactions. This activity proves that the literary and cultural approach is effective in instilling noble values ​​in the younger generation. Thus, this program is not only relevant for character education but also supports the preservation of local culture among students.